PELATIHAN CIPTA KREASI DAN PROSES SABLON BAGI KARANG TARUNA DESA TEGALHARJO, KECAMATAN EROMOKO, KABUPATEN WONOGIRI - Ani Rakhmawati (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The Screen printing is a technique for placing ink with a certain process on fabric in various shapes, images and colors. The skill of printing images on cloth and t-shirts has a prospect as an effort to improve creative skills and create independent job opportunities for young people. This screen printing process training was given to members of youth organizations in Tegalharjo Village, Eromoko District, Wonogiri Regency. So far, most of the livelihoods of the residents of Tegalharjo Village are farmers. The results of the training showed a significant improvement in skills and the youth's enthusiasm to open screen printing entrepreneurial opportunities to fill their spare time during the break after the planting season was over. Creation copyright training and screen printing processes are one of the roles of the academic community which are expected to be widely applied to entrepreneurial activities to reduce unemployment and create jobs in Tegalharjo Village.